Desenvolvimento de um compósito polimérico de pet mdf como material de engenharia: estudo exploratório - Santos, Caroline Gabriela Ferrazzo Borges dos (2019)
Solid waste management is a fundamental tool for dealing with the large amount of waste generated by human activities. Plastic and wood wastes that have characteristics that make it difficult to dispose of, require treatment alternatives aimed at sustainable disposal. Given this, the present study aimed to develop a polymer composite with the waste generated by the packagingindustry of the plastics (PET, polyethylene terephthalate) and furniture (waste MDF, medium density fiber) to obtain a composite with greater rigidity than polymeric materials.In the experimental study, the contents of residual MDF powder addition of 0%,2.5%, 5% and 10% in PET matrix were evaluated. It was also made the selection and characterization of the materials used as raw material (PET and MDF residual powder), and after the composite production, its thermal and mechanical properties were tested in order to verify the possibility of application of the product obtained as engineering material.The study indicated that it is possible to incorporate MDF residual powder into PET polymeric matrices, which may be an alternative for the eco-efficient use of solid waste.